GAMBARAN POLA ASUH ORANG TUA TERHADAP PERKEMBANGAN REMAJA DI SMP KRISTEN IMMANUEL GROGOL - Lyana Arsianti; Bernadetta Miranti Debora; Arni Safdiantina (STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2022)
Pattern foster parent is all the interactions between parents and children. Interaction herein referred attitudes expression value of attention in the care and training of their behavior. Parenting is a complex issue that includes action, interaction and reaction of all family members are father, mother, and each - each child. This study aims to look at the picture to the parents' parenting adolescent development. This study design using simple descriptive is one type of research methods to see the picture to the parents' parenting adolescent development in accordance with what it is. The number of samples used by 45 respondents in class VII and class VIII SMP Kristen Immanuel. These results indicate that people know students SMP Kristen Immanuel parenting parents apply the most dominant is the democratic parenting parents as much as 34 respondents (75.6%) while the value of being authoritarian parenting as much as 8 respondents (17.8%), and the lowest value of permissive parenting as much as three respondents (6.7%).